Reoperation and Complication Rates Following Patellar Fracture Repair with Plates: A Retrospective Analysis with Patient-Reported Outcomes at More than 1 Year of Follow-up. Issue 2 (12th April 2022) - Checketts, Jake X.; Scott, Jared; Fishbeck, Keith; Hart, Thomas; Pham, William; Dadgar, Azad; Calder, Mark; Norris, Brent L.
Abstract : Background: Recent work has suggested good clinical and functional results with dorsal surface plating of patellar fractures. The primary outcome measurement of this study was reoperation rates for patellar fractures that had been treated with dorsal plating. Methods: This work consists of a retrospective review of clinical and functional outcome data following repair of patellar fractures with dorsal plates. We obtained institutional review board approval for this study and conducted a review of 9 consecutive years of our group's trauma practice. We also contacted patients to assess patient-reported outcomes (PROs) after 12 months. Results: Eighty-five patellar fractures were treated with open reduction and internal fixation (ORIF) via plating over 9 years. Eight (9.41%) of the patients required reoperation. Of the 72 patients with complete follow-up of ≥12 weeks, 3 (4.17%) had nonunion of the fracture site and 4 (5.56%) had loss of reduction of the fracture. The average Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score among our sample was 18.84 (slight symptoms); 72.41% of the patients in our sample had slight or no symptoms at ≥12 months postoperatively. Conclusions: Our results indicated that plating of comminuted patellar fractures is a safe, viable treatment strategy. The PROs at ≥12 months of follow-up data were promising. Additionally, dorsal plating may allow for early return of function and less postoperative bracing. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.